2009
DOI: 10.1071/pc090217
|View full text |Cite
|
Sign up to set email alerts
|

Causes of mortality in stranded Common Dolphin (Delphinus sp.) from New Zealand waters between 1998 and 2008

Abstract: Post-mortem examinations provide valuable information on sources of mortality for marine mammal populations. However, no published data exist to describe causes of death in the New Zealand population of Common Dolphin (Delphinus sp.). In order to examine the proportion of human and non-human induced mortality affecting this population, necropsies were conducted on 133 individuals that stranded around the New Zealand coastline between 1998 and 2008. Of these, 92.5% (n=123) were found as beach cast carcasses, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
34
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 25 publications
0
34
1
Order By: Relevance
“…These results are in contrast to studies of the harbor porpoise in which the number of lung nematodes did not differ between young and old animals (Balbuena et al, 1994). Other studies have shown that young odontocetes are infected with lung nematodes (Woodward et al, 1969;Balbuena et al, 1994;Parsons et al, 1999;Parsons and Jefferson, 2000;Kuramochi et al, 2000;Bossart et al, 2003;Kuwamura et al, 2007;Stockin et al, 2009), raising the question of how the parasites are transmitted. Three possibilities have been suggested: 1) via the placenta, 2) via the milk, and 3) via an intermediate host as a prey species.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These results are in contrast to studies of the harbor porpoise in which the number of lung nematodes did not differ between young and old animals (Balbuena et al, 1994). Other studies have shown that young odontocetes are infected with lung nematodes (Woodward et al, 1969;Balbuena et al, 1994;Parsons et al, 1999;Parsons and Jefferson, 2000;Kuramochi et al, 2000;Bossart et al, 2003;Kuwamura et al, 2007;Stockin et al, 2009), raising the question of how the parasites are transmitted. Three possibilities have been suggested: 1) via the placenta, 2) via the milk, and 3) via an intermediate host as a prey species.…”
Section: Discussioncontrasting
confidence: 55%
“…No lung nematodes have been reported for Indo-Pacific bottlenose dolphins but, as noted, this species was only recently separated from the common bottlenose dolphin. Published reports of lung nematodes in common dolphins include Skrjabinalius guevarai from the Mediterranean (Raga et al, 1987), H. delphini from the United Kingdom (Gibson et al, 1998), and unknown species from New Zealand (Stockin et al, 2009). Arundel (1978) listed common dolphins among the species from which H. lagenorhynchi had been recorded in Australia but provided no reference.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the time spent foraging by the dolphins in this region being almost double that in neighboring open coastlines (Neumann , Stockin et al . ), a previous dietary study of stomach contents suggests common dolphins occupying Hauraki Gulf waters still travel offshore during the night to feed on the deep scattering layer (Meynier et al . ).…”
mentioning
confidence: 99%
“…While the reasons for this remain unclear, it is possible that the high usage of Hauraki waters for feeding (Stockin et al . ) and nursing purposes (Stockin et al . ) contribute to this scenario (Stockin and Orams ).…”
mentioning
confidence: 99%
“…The Hauraki Gulf is considered an important habitat for this species (Stockin and Orams 2009), and is documented for both its feeding (Stockin et al 2009 a ) and potential breeding (Stockin et al 2008 a ) importance to this population. However, human‐induced impacts including pollution (Stockin et al 2007), net entanglement (Stockin et al 2009 b ) and tourism (Stockin et al 2008 b ) are known to affect Delphinus . Surprisingly, although boat interactions with this species occur year round, potential acoustic impacts of these interactions remain unexamined.…”
mentioning
confidence: 99%